Determining the optimal lysine:calorie ratio for growth performance of pic nursery pigs - Schneider, J.D.; Tokach, Michael D.; Goodband, Robert D.; Nelssen, Jim L.; DeRouchey, Joel M.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
Two studies were conducted to evaluate the effects of increasing dietary lysine and energy density on nursery pig performance. Experiment 1 was organized as a combination of two simultaneous experiments,with one set of diets consisting of five treatments with increasing true ileal digestible (TID) lysine (1.11, 1.19, 1.26, 1.34, and 1.42%) and the second set of diets consisting of five treatments with increasing energy density (1,341, 1,408, 1,475, 1,542, and 1,609 kcal/lb). The highest level of both lysine and energy density (1.42% and 1,609 kcal/lb, respectively) were combined as one diet and used in both the lysine and energy-density titrations, to give a total of 9 diets for the 10 treatments. Pigs (PIC, avg BW = 22.5 lbs) were randomly allotted to eight replications with five pigs per pen, on the basis of BW. Overall (d 0 to 21) in Experiment 1, increasing TID lysine linearly increased (P<0.01) ADG and improved (linear, P<0.01) feed efficiency. Increasing energy density had no effect on ADG, but it decreased (linear, P<0.01) ADFI, which resulted in a linear (P<0.01) improvement in F/G. Regression analysis of the response surface was used to predict the optimal lysine: calorie ratios for ADG and F/G of 4.06 and 3.92 g lysine/Mcal ME for the PIC pigs used in this experiment. In Experiment 2, pigs (PIC, avg BW = 16.6 lbs) were fed diets with two different energy densities (1.34 or 1.49 Mcal ME/lb) with TID lysine:calorie ratios ranging from approximately 3.5 to 4.5 g/Mcal ME. There was an energy density × TID lysine:calorie ratio interaction observed for F/G. Pigs fed the low-energy diets had the greatest ADG, at a lysine: calorie ratio of 4.55. For pigs fed the high-energy diets, ADG improved as the lysine:calorie ratio improved to 4.26 g of TID lysine/Mcal ME. There was a quadratic (P<0.03) improvement in feed efficiency as the lysine:calorie ratios were increased for the pigs fed the low-energy diet, with the best F/G value observed at 4.55, but the pigs fed the high-energy diets experienced a linear (P<0.01) improvement in F/G as the lysine:calorie ratios were increased. These results suggest that the optimal lysine-to-calorie ratio is 4.26 to 4.55 g of TID lysine/Mcal ME for 20- to 50-lb PIC pigs in these facilities.
Swine research, 2005 is known as Swine day, 2005
Keywords: Swine; Lysine; Energy; Nursery pig